1984
DOI: 10.1111/j.1432-1033.1984.tb08265.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of aldolase isozyme mRNAs in fetal rat liver

Abstract: The regulation of aldolase isozyme expression during development was studied by measuring the concentrations of mRNAs coding for aldolase A and B subunits in fetal and adult rat liver. Poly(A)-containing RNAs were extracted from livers at various stages of development of fetal rats, and the aldolase A and B subunits in the in vitvo translation products of these RNAs ware analyzed immunologically. The content of aldolase B mRNA in 14-day fetal liver, measured quantitatively as translational activity, was somewh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…0~-Fetoprotein, a major fetus serum protein, and aldolase A, a muscle-type isozyme of aldolaso are known to be highly expressed in fetal liver and even in adult liver during hepatoc, arcinogenesis [10,11,18,19]. We …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…0~-Fetoprotein, a major fetus serum protein, and aldolase A, a muscle-type isozyme of aldolaso are known to be highly expressed in fetal liver and even in adult liver during hepatoc, arcinogenesis [10,11,18,19]. We …”
Section: Resultsmentioning
confidence: 99%
“…The proto-oncogenes, c-jun and c-fos, coding for nuclear proteins regulate cell growth and differentiation by controlling gene transcription through AP-1 enhancer element [13,14]. To further study abnormal gene expression in the liver of jvs mice, we determined the levels of c-jun, c-los, o~- highly in undifferentiated or de-differentiated hepatocytes [10,11,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…No differences were noted in the DNase footprinting pattern of the HNF-1 region when fetal and adult liver extracts were compared. Others have recently demonstrated that the liver-specific aldolase B gene is activated in late fetal rats as early as day 16 of gestation (28) and that its in vitro transcription is dependent on the presence of an HNF-1 binding site and a second site, designated AiF-B, that contained a CCAAT motif (40). These investigators demonstrated that the HNF-1 binding component increased at day 15 of gestation, but this increase did not correlate with in vitro transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Developmental Regulation of the Aldolase B 1600ABC/CAT Transgene in the Liver-Expression of the aldolase B gene in the liver is developmentally regulated; the mRNA is undetectable before day 14 of gestation, and from that stage to adult it was estimated to increase about 9-fold (Numazaki et al, 1984;Schapira et al, 1975). Using the line 7 expressing the 1600ABC/CAT transgene at a high level, we observed that developmental regulation of transgene expression mimics that of the endogenous aldolase B gene (Table II).…”
Section: Expression Of the Different Aldolase B-cat Transgenes Inmentioning
confidence: 99%